Respon Masyarakat Langsa Pasca Penerapan Qanun Aceh Nomor 11 Tahun 2018 Tentang Lembaga Keuangan Syariah - Ridha, Farid; Nurjanah, Nurjanah; Hamid, Abdul (TANSIQ: Jurnal Manajemen dan Bisnis Syariah, 2023)
One of the regions that has strong Sharia political will is Aceh Province where Aceh has special autonomy to form Sharia regional regulations or commonly called Qanun. Aceh Qanun No. 11 of 2018 concerning Sharia Financial Institutions (LKS), Qanun Number 8 of 2014 concerning Principles of Islamic Sharia requires that financial institutions that will operate in Aceh must carry out their activities based on Sharia principles. The purpose of this study is to find out the response of the people of Langsa City after the implementation of Qanun Number 11 of 2018 and the response of the people of Langsa City regarding Sharia Banks after the implementation of Qanun Number 11 of 2018. This study uses a qualitative approach. The subjects in this study were 7 people from Langsa City. The results of this study indicate that the people of Langsa City think that the existence of this qanun is actually quite good to support Aceh so that it can carry out all its activities based on Islam, especially in the financial sector. This Islamic bank also has a positive impact because the circulation of funds in Islamic banks must also be used for good things. Not only that, Islamic banks are also considered as a forum for Islamic-based transactions. It's just that I have a few problems that cause the transaction to be a bit disrupted.